Change and grassroots movement: reconceptualising women's hockey governance in Canada. (23rd May 2007) - Adams, Carly; Stevens, Julie
In Canada, female hockey governance structures vary as different regions of the country may better suit integrated or partially-integrated governance approaches based upon their unique local histories and individual dynamics. Indeed, the Ontario Women's Hockey Association (OWHA) is the only female hockey provincial association in Canada that endorses and endeavours to maintain a separatist philosophy. However, women's hockey governance in Canada as a whole has not progressed in a manner where the authority of female hockey participants and leaders has increased. This paper initiates dialogue about women's sport governance by utilising women's hockey in Canada and specifically a case study of the OWHA, as a context in which to develop a new perspective and renew efforts to place women's sport governance on the agenda. In order to develop a sport and governance dialogue for women's hockey specifically and women's sport more broadly, we present a theoretical discussion that integrates critical feminist and grassroots movement perspectives.